(untitled) (SAARC Journal of Agriculture, 2015)
The study was conducted at Rangtia, Shalchura and Dudhnoi villages under Jhenigati upazilla of Sherpur district in Bangladesh for phenotypic and morphometric characterization of indigenous chickens. Among three types of indigenous chickens, Non-descript Deshi were prominent (86%), compared to Cap Headed (10%) and Naked Neck (4%) and the overall mean body weight, back length, body circumference and pelvis width were 961.50 ± 17.79 gm, 152.70 ± 1.29 mm, 219.20 ± 1.89 mm and 25.57 ± .62 mm respectively. The prominent colors of plumage, shank, skin, earlobe and eggshell were multiple (24%), white (52%), white (89%), white & red (47%) and white (48%), respectively while 99% chickens had single comb. The highest correlation (0.70) was observed between body weight & body circumference followed by (0.36) between body weight & back length and (0.27) between body weight & pelvis width while eggshell color was significantly correlated with body weight (-0.48), body circumference (-0.41) and pelvis width (-0.26). However, comb type was significantly (p<0.05) affected body weight and pelvis width. But bird type had significant (p<0.05) effect on pelvis width only. Present study reveals that variations in some phenotypic characteristics have significant influence on the pelvis width and body weight while a little change in some morphometric traits may affect body weight of indigenous chickens in Bangladesh which may serve as important indicator trait(s) for future research on the conservation and development of indigenous chicken ecotypes in- situ. DOI: http://dx.doi.org/10.3329/sja.v12i2.21927 SAARC J. Agri., 12(2): 154-169 (2014)